Deadly connections : states that sponsor terrorism - Byman, Daniel, 1967- (Cambridge University Press, 2005)
Daniel Byman's hard-hitting book studies countries that support terrorist groups, examining the types of support they provide, their motivations, and the impact of such sponsorship. It also considers regimes that allow terrorists to raise money and recruit without providing active support. The experiences of Iran, Pakistan, Afghanistan, Syria, Saudi Arabia and Libya are recorded here.